Impact of Supplier Relationship Management on Supply Chain Performance in Kenya - Maina, Susan (International Journal of Supply Chain and Logistics, 2026)
Purpose: The purpose of this article was to analyze impact of supplier relationship management on supply chain performance in Kenya. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that effective Supplier Relationship Management (SRM) significantly improves supply chain performance in Kenya, particularly in areas such as delivery reliability, inventory turnover, and cost efficiency. Strong collaboration, trust, and communication between firms and their suppliers enhance operational efficiency and reduce transaction costs. Firms with formal SRM practices reported better performance outcomes, including timely deliveries and reduced stock outs. The research also highlighted the need for digital tools and employee training to optimize these practices. Unique Contribution to Theory, Practice and Policy: Transaction cost economics, social exchange theory resource-based view may be used to anchor future studies on the impact of supplier relationship management on supply chain performance in Kenya. For practical implementation, it is recommended that industry associations in vulnerable sectors, such as steel, aluminum, and fertilizers, establish sector-wide carbon accounting hubs. At the policy level, governments must pursue a dual-track strategy of negotiation and domestic transformation.